Оцінка впливу інкрустації та інокуляції насіння гороху хімічними та біологічними препаратами на розміри симбіотичної фіксації за різних умов живлення - Лемішко, Світлана Миколаївна; Lemishko, Svіtlana (Херсонський державний аграрно-економічний університет, 2020)
Максимальний рівень азотфіксації був відмічений за інкрустації насіння препаратами фунгіцидної і рістрегулюючої дії, а саме, біопрепаратів Агат-25 К і Реаком-С боби. Під їх дією розміри симбіотичної фіксації у сорту Харківський янтарний були більше на фоні без застосування добрив, на 26 і 22 % більше, ніж на контролі (обробка водою). Ці препарати зберігали таку ж дію при дещо менших показниках симбіотичної азотфіксації на фоні із застосуванням добрив (N20P40). Приріст азотфіксації становив 14 та 26% від застосування Агат-25 К і Реаком-С боби на удобреному фоні в порівнянні з контролем. Ці залежності зберігалися на фоні із застосуванням добрив (N20P40). Розміри азотфіксації були дещо нижчими при вирощуванні гороху Харківський еталонний у порівнянні з показниками сорту Харківський янтарний на всіх варіантах досліду. Розміри симбіотичної азотфіксації у варіантах з інокуляцією насіння гороху бактеріальними препаратами на контролі були приблизно на тому ж рівні, що і в досліді з інкрустацією. Використання для інокуляції зерна сорту Харківський янтарний фосформобілізуючих бактерій на фоні без мінеральних добрив сприяло підвищенню азотфіксації на 32%. Зростання азотфіксації під впливом поліміксобактерину і ризогуміну складало 22 і 25% відповідно. Найбільший рівень зростання азотфіксації спостерігали при поєднанні фосформобілізуючих бактерій з поліміксобактерином (33,0%). Найкращі показники симбіотичної азотфіксації без мінеральних добрив одержані при поєднанні препаратів Кристалон, Актофіт і Агат–25 К (61,5 кг/га) при обробці рослин гороху сорту Харківський янтарний (майже на 30% вище, ніж на контролі). Усі інші комбінації препаратів сприяли зростанню азотфіксації на 14–19 % у порівнянні з контролем. Аналогічні тенденції та закономірності характерні також і для сорту Харківський еталонний. The maximum level of nitrogen fixation was observed after seed incrustation with preparations with a fungicidal and growth regulating effect (biopreparations Agate-25 K and Reacom-C beans). The symbiotic fixation in the Kharkiv yantarniy variety under their action was 26 and 22% higher against the background without fertilizer application than in the control (water treatment). These preparations maintained the same effect at slightly lower rates of symbiotic nitrogen fixation on the background with the use of fertilizers (N20P40). The increase in nitrogen fixation was 14 and 26% from the use of Agate-25 K and Reacom-C beans on a fertilized background compared to the control. These dependences were maintained against the background with the use of fertilizers (N20P40). The level of nitrogen fixation was slightly lower in the growing of Kharkiv etalonniy peas compared to the indicators of the Kharkiv yantarniy variety in all variants of the experiment. The size of the symbiotic nitrogen fixation in the variants after pea seeds inoculation with bacterial preparations on control was approximately at the same level as in the experiment with incrustation. The use of phosphorus – mobilizing bacteria for grain inoculation of the Kharkiv yantarniy variety on the background without mineral fertilizers contributed to the increase of nitrogen fixation by 32%. The increase in nitrogen fixation under the influence of polymyxobacterin and rhizohumine was 22 and 25%, respectively. The highest level of nitrogen fixation was observed in the combination of phosphorus-mobilizing bacteria with polymyxobacterin (33.0%). The best level of symbiotic nitrogen fixation without mineral fertilizers was obtained with a combination of Kristalon, Aktofit and Agate-25 K (61.5 kg / ha) in the treatment of Kharkiv yantarniy pea plants (almost 30% higher than in the control). All other combinations contributed to an increase in nitrogen fixation by 14-19% compared with the control. Similar trends and patterns are characteristic of the Kharkiv etalonniy variety as well.
Evaluation of the influence of incrustation and inoculation of pea seeds with chemical and biological preparations on the size of symbiotic fixation under different nutrition conditions
Keywords: горох; peas; інкрустація; incrustation; інокуляція; inoculation; азотфіксація; nitrogen fixation; біопрепарати; biofungicide; дози добрив; growth stimulant